Neutrophil extracellular traps as a novel biomarker to predict recurrence-free and overall survival in patients with primary hepatic malignancies. Issue 2 (February 2021) - Kaltenmeier, Christof T.; Yazdani, Hamza; van der Windt, Dirk; Molinari, Michele; Geller, David; Tsung, Allan; Tohme, Samer
Abstract: Background: The incidence of primary hepatic malignancies including Hepatocellular carcinoma (HCC) and cholangiocarcinoma (CC) is on the rise. (i) Surgery remains the mainstay of potential curative treatment, however the vast majority of patients will recur and not be amenable to curative therapy. (ii) Inflammation has been associated with poor prognosis, however there is no preoperative marker that can predict recurrence-free- or overall survival. Our aim is to correlate inflammation measured as neutrophil extracellular traps (NETs) with survival. Methods: A retrospective analysis was performed using sera/tissue from patients with hepatic malignancies. NET levels were measured in the serum (MPO-DNA) or tumor (Cit-H3). Log rank analysis for RFS/OS was performed. Results: Cancer patients had higher pre-surgery MPO-DNA levels compared to healthy individuals (healthy vs cancer: 2.6 ± 1.0 ng/ml vs 34.7 ± 2.13 ng/ml; p < 0.0001). High pre-surgery serum NET levels were associated with shorter RFS/OS compared to those with low levels (RFS-HCC: HR: 2.91, 95% CI: 1.61–5.26, p < 0.0001, RFS-CC: HR: 3.22, 95% CI: 1.33–7.77 p < 0.0093). High Cit-H3 tumor levels similarly predicted shorter RFS/OS. Conclusion: The current study shows a correlation between pre-operative NET levels and survival. Studying NET formation as a biomarker pre-surgery can help identify patients that could benefit from closer follow-up due to higher risk for recurrence.